Myth or Reality: Self-Assessment Is Central to Effective Curriculum in Anatomical Pathology Graduate Medical Education. (10th May 2021) - Lu, Fang-I; Takahashi, Susan Glover; Kerr, Carolyn
Self-assessment, a personal evaluation of one's professional attributes and abilities against a perceived norm, has frequently been cited as a necessary component of self-directed learning and the maintenance of competency within regulated health professions, including the medical professions. However, education research literature has consistently shown uninformed personal global assessment of performance to be inaccurate in a variety of contexts, and have limited value in a workplace-based curriculum. Incorporating known standards of performance with internal and external data on the performance improves a learner's ability to accurately self-assess. Selecting content suitable for self-assessment, providing explicit assessment standards, encouraging feedback-seeking behaviors, supporting a growth mindset, and providing quality feedback in a supportive context are all strategies that can support learner self-assessment, learner engagement in reflection, and action on feedback in Anatomical Pathology graduate medical education.